Simulation and Experimental Measurement of Liquid Crystal Polymer Directionality During Melt Processing - Sullivan, Anthony. (Tufts University. Tisch Library., 2019)
Liquid crystal polymers (LCPs) comprise a class of high-performance, melt-processable materials that have historically fallen short of widespread adoption in industry due to their anisotropic bulk behavior. The anisotropy is a direct result of the unique polymer microstructure, and the ability to predict the polymer morphology generated during manufacturing is essential to isotropic material process design. This dissertation presents the implementation of a practical modeling tool to simulate the evolution of LCP directionality during melt processing. The hybrid methodology leverages commercial CFD software to first simulate the polymer flow through full-scale processing geometries, followed by post-processing calculations to predict the orientation state of the director field. Parallel investigations of LCP directionality during injection molding and cast film extrusion are presented to demonstrate the robustness of the modeling tool across two common melt processing methods. Wide-angle x-ray scattering (WAXS) is used to experimentally validate the orientation states predicted by the model, and mechanical, thermal and dielectric material testing confirm the strong dependence of macroscopic behavior on the polymer microstructure. Comparison of simulations and WAXS verify the ability to not only predict bulk orientation, but also the intricacies of the hierarchal structure, specifically the skin and core morphologies, and their relative amounts. Furthermore, the full suite of simulations, WAXS, and material testing elucidate the LCP structure-property-processing relationships that are critical to driving isotropic material process design.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Michael Zimmerman, and Anil Saigal.; Committee: Ayse Asatekin, and Jay Whitacre.; Keywords: Mechanical engineering, and Materials Science.